Prevalence and Determinants of Metabolic Syndrome in Schizophrenia Patients Treated with Antipsychotics Medications - Mohamed Alsanosy Rashad (Journal of Schizophrenia Disorders And Therapy, 2019)
Objectives This study was designed to assess the demographic characteristics, prevalence of metabolic syndrome (MetSy) among patients with schizophrenia in Saudi Arabia. Methods This is a disease-oriented and observational study. Schizophrenia was defined by DSM-IV criteria. MetSy were assessed based on the international criteria (NCEP-ATP III and AHA/NHLB). Results 90% of the participants are without a university degree and 56.4% are single. Chronic and acute cases of schizophrenia were 95% and 5%, respectively. The treatment of schizophrenia was combination therapy and monotherapy with percentages of 56% and 44%, respectively. Systolic and diastolic blood pressures were 121.92±11.07 mmHg and 77.29±0.45 mmHg, respectively. Surprisingly, all patients have abnormal HDL. A mean waist circumference of 90.23±14.88 cm for men, and 93.38±15.28 cm for women. The analysis of 101 patients showed a prevalence of the MetSy is 15.8%. Chi-square test of independence showed lack of independency of MetSy on type of therapy. Modeling of MetSy and risk factors was also conducted. Conclusion The metabolic syndrome is greatly established among schizophrenic patients. It signifies a vital hazard for metabolic and cardiovascular ailments. Evaluation of the incidence and examining of the related threats of the metabolic syndrome should be an element of the clinical managing of patients cured with antipsychotics.
Keywords: Schizophrenia